Analisis Efisiensi Usahatani Bawang Merah Lembah Palu Di Kecamatan Sigi Biromaru Kabupaten Sigi Analysis of efficiency of Lembah Palu Shallot Farming Systemin Sigi Biromaru Sub District of Sigi District - Muhammad Asy’ Ary; Lien Damayanti; Effendy Effendy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
ABSTRACTThe aim of the research was to determine the technical, allocative and economical efficiencies of Lembah Palu shallot farming systems and factors affecting their technical efficiency.  It was conducted in Sigi Biromaru sub district where Bulupountu Jaya, Soulowe, and Oloboju villages located.  Forty farmers were selected using a random sampling technique.  Data collected was analyzed using the production function of stochastic frontier Cobb-Douglas, and input approaches.  The results showed that land size area, seeds, fertilizer and labors significantly affected the production of Lembah Palu shallot at 95% confident level.  The shallot farming systems in Palu were technically efficient but allocatively and economically not yet efficient with the values of 0.98, 0.66 and 0.65, respectively.  Such factors as non-formal and formal education, farming experiences, and family dependents were not significantly affected the technical efficiency. Keywords: Efficiency, production factors, and stochastic frontier.